Strategi Komunikasi Institusional: Model Implementatif Pembangunan Reputasi dan Daya Saing Politeknik Vokasi - Roni Setia Nugraha; Edi Tri Prayitno; Ade Irda Savitri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Achieving superior institutional accreditation places a university in a new strategic phase that demands more focused and sustainable communication management. This study analyzes the communication strategy of Politeknik Caltex Riau after gaining superior accreditation and explores the role of communication in building reputation and competitiveness within vocational higher education. Using a qualitative case study approach, data were collected through in-depth interviews with key informants, observation of communication practices, and analysis of institutional documents and digital content. Thematic analysis was applied to identify patterns and meanings in the strategies used. The findings show a shift in communication orientation from promotional activities to a reputation-based approach grounded in performance evidence and institutional values. The post-accreditation strategy is supported by the internalization of IDEAL values in internal communication, consistent institutional identity management, strategic use of digital media as the institution’s main representation, and strengthened external relations and stakeholder collaboration. This integrated approach contributes to increased public trust and improved stakeholder perceptions. The study concludes that communication after superior accreditation functions as a strategic tool for enhancing reputation and competitiveness in vocational higher education. These findings offer both practical and conceptual insights to guide the development of institutional communication strategies in similar educational settings.